Peluang Dan Tantangan Bisnis Pariwisata Di Era New Normal - Muhamad Ali; Huzain Jailani; Rohaeniah Zein (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2022)
The Covid-19 pandemic has had a huge impact both in terms of health which has claimed many lives, as well as social and economic causes which have caused more than 25 million people to lose their jobs, paralyzed the tourism and MSME sectors due to social restriction policies and disrupted supply chains. After running for more than 2 years, signs of decreasing the spread of covdi along with the administration of vaccine doses 1, 2 and 3 to almost all people have slowly been given to almost all people, the government has begun to reopen the community's socio-economic activities with supervision and standards proportionally regulated health protocols. We then refer to this situation as the new normal situation. This study focuses on identifying challenges and opportunities for the tourism business in the new normal period, and discusses strategies that need to be implemented to face challenges and take advantage of tourism business opportunities in the new normal period. The method used is descriptive qualitative using content analysis and literature study approaches. Based on the results of the study, various strategies that need to be carried out can be short term which include providing assistance as a form of support to strengthen business actors in the tourism sector and affected MSMEs through various schemes and policy packages that have been carried out by the government, compiling and establishing SOPs for guarantee the security and safety of tourists through strict health protocol standards. Then for the medium term strategy is carried out by trying to collaborate with all groups in the development of the tourism sector and MSMEs through a pentahelic strategy between academics, business actors, government, society and the media. And the long-term strategy is to prepare a better and more fundamental system while continuing to map potential destinations by continuing to develop and maximize the potential of domestic tourists and prepare for the arrival of foreign tourists.